Investigating Factors Impelling the innovation performance: A perspective from Internal Corporate New Business Venturing on Manufacturing Industry - Prio Utomo; Florentina Kurniasari (ADI Publisher, 2020)
Today’s businesses must innovate to survive in record time to keep up with constant technology advancements and continual customer demand. And organization initially attempts to develop innovation from the inside by leveraging their employees. This study provides insight on effects that influence the entrepreneurial attitude toward the innovation performance in the context of searching for new business through internal corporate new business venturing programs. There are 71 participants of an internal business venture program in manufacturing company responded in regard to their intrapreneur attitude and Corporate Entrepreneurship Climate toward their innovation performance. This model analyzed using Structural Equation Model – Partial Least Square (SEM-PLS) with the result that only internal locus of control and market orientation are two attitudes that significantly relates to innovation performance, and these attitudes are compelled by management support and organization boundary.